Introductory Notes on Abdullah Munshi’s Hikayat Binatang - Baharuddin Ahmad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
The first school textbook written in the Malay language (1846) is Bahwa Ini Hikayat Binatang (On the Chronicle of Animals) on the subject of Zoology, which is an important part of Natural History. It discusses animal species, their habitats, their uses by men, their bodily features in great details and their habits as well as the geographical areas and climates of their countries of origin; the area where they were first found in those countries and the climates and how they were later brought and transported to other places where they were again reared therein as their second home. The book is probably the first Malay printed work in Latin script on Natural History. It is quite possible that it is also the first work on modern scientific knowledge in Malay.